Effect of Video Education on Dengue Knowledge in Adolescents - Agnes Siti Kusminah; Atira; Budi Rianto; Emy Salmiyah (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2026)
Dengue hemorrhagic fever remains a significant public health problem, particularly in endemic areas where adolescents are also at risk of exposure. Limited knowledge regarding transmission, symptoms, and prevention may contribute to inadequate preventive behavior. Educational media that are attractive and easy to understand are needed to improve adolescent knowledge, including video-based health education. This study aimed to determine the effect of video media on improving adolescents’ knowledge about dengue hemorrhagic fever. This quasi-experimental study used a one-group pretest-posttest design. The participants were 100 students in grades VII-IX at MTs Darussalam, Melong, Cimahi, recruited through total sampling. A five-minute dengue education video was shown three times during the intervention session. Knowledge was assessed immediately before and after the intervention using an 11-item study-specific questionnaire. Data were summarized descriptively and analyzed using the Marginal Homogeneity test. Before the intervention, most respondents had poor knowledge (64.0%), while only 15.0% had good knowledge. After the intervention, the proportion with good knowledge increased to 54.0%, while poor knowledge decreased to 17.0%. The Marginal Homogeneity test indicated a statistically significant change in knowledge level (p < 0.001). Video-based health education was associated with a significant improvement in adolescents' dengue knowledge. This medium may be considered as an accessible health-promotion strategy for school-age populations.